2016
DOI: 10.1097/imi.0000000000000297
|View full text |Cite
|
Sign up to set email alerts
|

Attaining Proficiency in Robotic-Assisted Minimally Invasive Esophagectomy While Maximizing Safety during Procedure Development

Abstract: Objective Robotic-assisted minimally invasive esophagectomy (RAMIE) is an emerging complex operation with limited reports detailing morbidity, mortality, and requirements for attaining proficiency. Our objective was to develop a standardized RAMIE technique, evaluate procedure safety, and assess outcomes using a dedicated operative team and 2-surgeon approach. Methods We conducted a study of sequential pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 15 publications
3
45
0
Order By: Relevance
“…This commentary's senior author's (I.S.S.) own extensive experience with the RAMIE Ivor Lewis approach at both Memorial Sloan Kettering Cancer Center and the University of Pittsburgh Medical Center supports this hypothesis (8,12). In a collective experience of 125 cases, there was 1 operative mortality at 90 days, median lymph node counts were greater than 25, significant anastomotic leak occurred in 4-6% of patients, and complete resection was achieved in over 90% of patients.…”
Section: Meticulous Attention To Clear Identification Of Vital Anatomymentioning
confidence: 53%
See 2 more Smart Citations
“…This commentary's senior author's (I.S.S.) own extensive experience with the RAMIE Ivor Lewis approach at both Memorial Sloan Kettering Cancer Center and the University of Pittsburgh Medical Center supports this hypothesis (8,12). In a collective experience of 125 cases, there was 1 operative mortality at 90 days, median lymph node counts were greater than 25, significant anastomotic leak occurred in 4-6% of patients, and complete resection was achieved in over 90% of patients.…”
Section: Meticulous Attention To Clear Identification Of Vital Anatomymentioning
confidence: 53%
“…When they do occur, surgeons must use quick and sound judgement in determining whether these events can be managed minimally invasively, or require urgent conversion to open operations (10). During attainment of the learning curve, estimated at 35-50 cases for experienced esophageal surgeons, strong consideration should be given to conversion for technically challenging portions of the case as experience is gained (7,8).…”
Section: Meticulous Attention To Clear Identification Of Vital Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the initial institutional experience has been greatly aided by the extensive previous experience and expertise of the two senior authors of this publication (IS Sarkaria and JD Luketich). The previously published experience by one of the senior authors (IS Sarkaria) at Memorial Sloan Kettering Cancer Center reported excellent outcomes in 100 patients undergoing RAMIE with an anastomotic leak rate of 6%, 0% 30-day mortality, and a 90-day mortality rate of 1% (12). The robotic platform offers many potential advantages to this specific operation.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic console time with this innovative procedure was reported to be significantly reduced after the initial six patients 22. A significant reduction in total operative time was identified after the initial 20 or 30 cases 27, 28…”
Section: Learning Curvementioning
confidence: 92%